Mobilizing Islamic Finance for Infrastructure Public-Private Partnerships - World Bank Group; Islamic Development Bank Group (World Bank, Washington, DC, 2017)
This public-private infrastructure advisory facility (PPIAF) - funded report aims to discuss and disseminate information on how Islamic finance has been applied in infrastructure projects through public-private partnership (PPP) schemes, what the structural challenges and solutions are, and what can be done to deepen and maximize the use of Islamic finance for this purpose. This report has two broad dimensions. The first is to enhance the understanding of Islamic finance building blocks as they relate to financing infrastructure PPP projects, and the second, and perhaps less well understood, is to explore how the building blocks of Islamic finance can fit within a PPP context. This report paves the way for providers of Islamic finance capital to become partners in infrastructure development and thus contribute to its overall global financing pool.